2015
DOI: 10.1021/ie504305s
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Helical Nanofibers via Co-Electrospinning

Abstract: Co-electrospinning is a new branch of nanotechnology for producing composite nanofibers with collective functions and special fiber structures. Helical fibers in nanoscale have been of increasing interest because of their unique characteristics. In this work, we report the fabrication of the helical nanofibers with polyurethane and poly­(m-phenylene isophthalamide) by the co-electrospinning system with an off-centered core–shell spinneret. High-speed photography and three-dimensional (3D) electric field simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…It is shown that the helical microfiber has a three‐dimensional spiral shape, which resembles the helical coiling of the plant tendril (calabash tendril) presented in Figure (c). It is worth nothing that these helical structures are different from the curved structures with much larger coiling diameters of the buckling fibers, which are believed to result primarily from the impinging of the fibers on the collector …”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the helical microfiber has a three‐dimensional spiral shape, which resembles the helical coiling of the plant tendril (calabash tendril) presented in Figure (c). It is worth nothing that these helical structures are different from the curved structures with much larger coiling diameters of the buckling fibers, which are believed to result primarily from the impinging of the fibers on the collector …”
Section: Resultsmentioning
confidence: 99%
“…on the study of cucumber tendril helices. The calculation of k has been introduced in our previous study . The larger the helical curvature is, the tighter the helical structure is.…”
Section: Resultsmentioning
confidence: 99%
“…It is straightforward to extrude different polymer solutions together into one single jet to produce a heterogenous fiber, and the adjustable experiment setup of electrospinning makes it convenient to accomplish this. By using a multichannel springe where each polymer solution can flow separately in the spring and merge together at the outlet ( Figure 16 a), it is possible to acquire fibers with various internal structures such as core-shell [ 123 ], off-centered [ 124 ] and side-by-side [ 125 , 126 ] ( Figure 16 b). The constitution usually includes a soft elastomer and a rigid elastomer.…”
Section: Helical Structures Mimicking Tendril’s Coilingmentioning
confidence: 99%
“…The blue and red represent different polymers. ( a ) is from [ 124 ], reprinted with permission, copyright (2015) American Chemical Society.…”
Section: Figurementioning
confidence: 99%